Detecting Ultra-Violet Radiation by Using Titanium Dioxide Nanoparticles - Kargan, Naser Hatefi; Aliahmad, Mousa; Azizi, Samereh (Scientific Research, 2012)
In this paper sensitivity of chemically synthesized titanium dioxide (TiO2) nanoparticles to ultra-violet (UV) radiation is investigated. For this purpose three types of ultra-violet photodetectors were fabricated, one with as-synthesized TiO2 nanoparticles, another one with TiO2 nanoparticles annealed at 600˚C, and the third one with TiO2 nanoparticles annealed at 800˚C. In each case the annealing time duration was one hour. The photodetectors were fabricated on glass slides where on them a thin layer of fluorine doped tin oxide (FTO) was deposited by spray pyrolysis. The results show that all photodetectors are sensitive to UV radiation where the photodetectors fabricated from annealed TiO2 nanoparticles are more sensitive than the photodetectors fabricated from as-synthesized TiO2 nanoparticles.
Keywords: Ultra-Violet Photodetector; Titanium Dioxide; Nanocrystals; Nanoparticles